Diversification in Monkeyflowers: An Investigation of the Effects of Elevation and Floral Color in the Genus Mimulus. (5th January 2014) - Ogutcen, Ezgi; Hamper, Brooklyn; Vamosi, Jana C.
Abstract : The vast diversity of floral colours in many flowering plant families, paired with the observation of preferences among pollinators, suggests that floral colour may be involved in the process of speciation in flowering plants. While transitions in floral colour have been examined in numerous genera, we have very little information on the consequences of floral colour transitions to the evolutionary success of a clade. Overlaid upon these patterns is the possibility that certain floral colours are more prevalent in certain environments, with the causes of differential diversification being more directly determined by geographical distribution. Here we examine transition rates to anthocyanin + carotenoid rich (red/orange/fuschia) flowers and examine whether red/orange flowers are associated with differences in speciation and/or extinction rates in Mimulus . Because it has been suggested that reddish flowers are more prevalent at high elevation, we also examine the macroevolutionary evidence for this association and determine if there is evidence for differential diversification at high elevations. We find that, while red/orange clades have equivalent speciation rates, the trait state of reddish flowers reverts more rapidly to the nonreddish trait state. Moreover, there is evidence for high speciation rates at high elevation and no evidence for transition rates in floral colour to differ depending on elevation.